Identification of chemical compounds of 70% ethanol extract of chinese betel leaves (Peperomia pellucida) from blora regency - Kenanga, Gigih (Journal of Health Management and Pharmacy Exploration, 2024)
Indonesia is rich in various plants, one of which is the Chinese Betel (Peperomia pellucida). This study aims to identify the chemical compounds of 70% ethanol extract from Chinese betel leaves in Blora Regency. The identification method is by laboratory observation with Thin Layer Chromatography (TLC). The results of the TLC test with the highest or best values are saponins, tannins, triterpenoids which can be seen by looking at the difference between the high points of the stains on the sample and the comparator. The active content in saponins, tannins and triterpenoids functions as a source of antibacterials, increasing the immune system. Flavonoids also have anti-inflammatory content (anti-inflammatory on the skin), as antioxidants and as histamine. Saponins as antibacterials with a mechanism that reacts with porins (transmembrane proteins) on the outer membrane of the bacterial cell wall, forming strong polymer bonds that damage the porins and can inhibit the growth of antibacterials.